Intra-household allocation of resources: inferences from non-resident fathers' child support payments - John Ermisch; Chiara Pronzato (University of Essex, Institute for Social and Economic Research (ISER), 2006)
A large proportion of divorced and separated fathers form new partnerships. The new partners preferences are likely to put a much lower weight (if any) on expenditures on the mans children from his previous union. As a consequence, his own and his partners income would have different impacts on his child support payments if partners relative incomes affect bargaining power in household decisions. This paper exploits within-father variation in the British Household Panel Survey (1991-2003) to estimate the impacts of partners incomes on child support payments. We find that a higher share of fathers income in household income increases the probability of paying child support and its amount relative to household income.
Keywords: 330